STUDI KASUS ASUHAN KEBIDANAN KOMPREHENSIF PADANY.N DENGAN KEKURANGAN ENERGI KRONIK DI PRAKTIK MANDIRI BIDAN “ENDANG RIYANTI. S, ST”KECAMATAN AMBARAWA KABUPATEN PRINGSEWU TAHUN 2020 - Riska Putri Utami; Siti Rohani; Psiari Kusuma Wardani; Desi kumalasari (Universitas Aisyah Pringsewu, 2020)
Chronic Energy Deficiency (KEK) is one of the malnutrition problems that often occurs in pregnant women, which is caused by lack of energy in a long period of time or years. KEK is also one of the causes of bleeding in pregnant women. Based on the results of a survey at PMB EndangRiyanti S, ST in December there were 2 KEK pregnant women. One of them, Mrs. N is 21 years old G2P1A0 and there are 19 KEK pregnant women in the Ambarawapuskesmas. The results in the implementation of midwifery management interpret basic data, identify, make diagnoses and provide midwifery care, there are some concordance and differences between the theory and reality in this case both occur in pregnant women with KEK. With the results in the care of Mrs.